2000
DOI: 10.1097/00000542-200004000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Both EMLA and Placebo Cream Reduced Pain during Extracorporeal Piezoelectric Shock Wave Lithotripsy with the Piezolith 2300

Abstract: EMLA and placebo creams under occlusive dressing reduced pain during EPSWL. The presence of the cream itself as a coupling medium contributed to analgesia. This may be a useful, simple, safe, and economical adjuvant technique to reduce pain during immersion EPSWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…However, EMLA cream did not appear superior to placebo. 15 One of the limitations of our study is that stone analysis was not completed for our patients. The other limitation is that the stone-free rates were not compared between first and second sessions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, EMLA cream did not appear superior to placebo. 15 One of the limitations of our study is that stone analysis was not completed for our patients. The other limitation is that the stone-free rates were not compared between first and second sessions.…”
Section: Discussionmentioning
confidence: 94%
“…10 Anxiety points were calculated in the following manner: of the 20 questions on the form, questions 1, 2, 5, 8,10,11,15,16,19, and 20 were reverse statements. The total points obtained from the reverse statements were subtracted from the total points of remaining direct statements.…”
Section: Anxiety and Pain Scoring Systemmentioning
confidence: 99%
“…They consider EMLA a valuable anesthetic alternative in ESWL, especially in patients in whom intravenous anesthesia cannot be used. Additionally, Tritrakarn et al [13] reported that EMLA cream may be a simple, safe and economical technique to reduce pain during ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…When SWL first began in 1980, it was performed with the patient under epidural or general anesthesia (1)(2)(3)(4)(5). Modifications in lithotripters over last two decades have made SWL a less painful experience (6). Most current lithotripters are powered by an electromagnetic generator.…”
Section: Introductionmentioning
confidence: 99%